2014
DOI: 10.1021/ja412105t
|View full text |Cite
|
Sign up to set email alerts
|

The Presence of an Air–Water Interface Affects Formation and Elongation of α-Synuclein Fibrils

Abstract: The aggregation of human α-Synuclein (α-Syn) into amyloid fibrils is related to the onset of multiple diseases termed synucleinopathies. Substantial evidence suggests that hydrophobic-hydrophilic interfaces promote the aggregation of amyloidogenic proteins and peptides in vitro. In this work the effect of the air-water interface (AWI) on α-Syn aggregation is investigated by means of thioflavin T binding measurements, dynamic light scattering, size-exclusion chromatography, electron microscopy, and atomic force… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
241
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 251 publications
(249 citation statements)
references
References 58 publications
(145 reference statements)
7
241
0
1
Order By: Relevance
“…Expression and Purification of ␣-Synuclein-Recombinant wild-type (WT) human ␣-Syn and the ␣-Syn variant ␣-Syn(C141) were overexpressed in the Escherichia coli strain BL21 Star TM (DE3) pLysS (Invitrogen) and purified as described previously (62). 2 H, 15 N-, and 13 C, 15 N-labeled human ␣-Syn were produced using standard M9 minimal medium (63) based on D 2 O (Isotec) and H 2 O, respectively, supplemented with 3 g/liter 13 C glucose (Isotec), and 1 g/liter 15 NH 4 Cl (Isotec).…”
Section: Methodsmentioning
confidence: 99%
“…Expression and Purification of ␣-Synuclein-Recombinant wild-type (WT) human ␣-Syn and the ␣-Syn variant ␣-Syn(C141) were overexpressed in the Escherichia coli strain BL21 Star TM (DE3) pLysS (Invitrogen) and purified as described previously (62). 2 H, 15 N-, and 13 C, 15 N-labeled human ␣-Syn were produced using standard M9 minimal medium (63) based on D 2 O (Isotec) and H 2 O, respectively, supplemented with 3 g/liter 13 C glucose (Isotec), and 1 g/liter 15 NH 4 Cl (Isotec).…”
Section: Methodsmentioning
confidence: 99%
“…α-Synuclein Samples The proteins (wild type α-synuclein and the E57K variant) were expressed, purified, and prepared as samples for the experiments as described previously (17 ). The purity of the proteins was at least 98%.…”
Section: Methodsmentioning
confidence: 99%
“…Previous work has shown that the process of nucleation of α-synuclein amyloid fibrils is likely to be heterogeneous and catalyzed by environmental features, such as air-water interfaces (26,27), lipid bilayers (28), SDS micelles and other anionic surfactants (11,29,30), or artificial interfaces such as the coatings of containers or stir bars (31). In addition, mechanical action, such as shaking and stirring, is often used to accelerate the aggregation of α-synuclein (32).…”
Section: Primary Nucleation and Fragmentation Can Be Selectively Enhamentioning
confidence: 99%